Validation of the Italian version of the Charcot‐Marie‐Tooth Health Index. Issue 3 (24th June 2020) - Pisciotta, Chiara; Ciafaloni, Emma; Zuccarino, Riccardo; Calabrese, Daniela; Saveri, Paola; Fenu, Silvia; Tramacere, Irene; Genovese, Filippo; Dilek, Nuran; Johnson, Nicholas E.; Heatwole, Chad; Herrmann, David N.; et al.
Abstract: The Charcot‐Marie‐Tooth Health Index (CMT‐HI) is a disease‐specific patient‐reported outcome measure measuring overall disease burden in Charcot‐Marie‐Tooth (CMT) patients, designed for natural history studies and clinical trials in English‐speaking affected individuals. We developed and validated its Italian Charcot‐Marie‐Tooth Health Index (I‐CMT‐HI) version. The questionnaire was translated and culturally adapted from source into Italian by two neurologists experienced in CMT and neuromuscular disorders (NMDs). The two translations were reviewed by a panel of seven experts in CMT and NMD. The provisional version was back‐translated into English by a professional translator. The definitive Italian version was developed during a consensus teleconference by the panel and a patient representative from ACMT‐Rete. A series of clinically and genetically characterized CMT patients completed the final questionnaire; 11 participated in a test‐retest reliability assessment of the instrument. The I‐CMT‐HI was administered to 30 CMT patients (13 CMT1A, eight CMTX1, two CMT1B, two CMT1E, two CMT2I, one CMT2A, one CMT2N, one distal Hereditary Motor Neuropathy), with test‐rest in 11:14 females and 16 males, aged (mean ± SD) 48.0 ± 16.4 years (range 18‐81), with CMT Examination Score (CMTES) = 10.0 ± 4.4 (range 2‐18). The I‐CMT‐HI mean total score was 29.4 ± 21.2 (range 0.1‐60.3). The I‐CMT‐HI showed a high test‐retest reliability: intraclass correlation coefficient = 0.95 (95% confidence interval, 0.84‐0.99). No patient had difficulty in completing the questionnaire and none reported any problem with the questions' formulation. The total CMT‐HI score was positively correlated with age and CMTES, with higher disease burden with increasing age and disease severity according to the CMTES. The I‐CMT‐HI is now ready for use in clinical studies in the Italian population.